Radical Islam and the revival of medieval theology - Lav, Daniel (Cambridge University Press, 2012)
With a scope that bridges the gap between the study of classical Islam and the modern Middle East, this book uncovers a profound theological dimension in contemporary Islamic radicalism and explores the continued relevance of medieval theology to modern debates. This combines classical Islamic scholarship with a deep familiarity with contemporary radicalism and offers compelling new insights into the structure of modern radical Islam.